2019
DOI: 10.24874/ijqr13.02-08
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Service Quality on Users' Behavioural Intentions in Developing Countries: A Cross-Sectional Study in Cape Verde's Public Hospitals

Abstract: The study analyses the influence of perceived service quality and patients' satisfaction on behavioral intentions, as well as the role of the institutional image in this chain of relations, studying also the applicability of the PAKSERV scale in the Cape Verdean health care context. Data collection was conducted through a self-administered questionnaire applied to emergency services users in two public hospitals in Cape Verde. Results of a structural equation modelling approach confirm the influence of perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…According to Choudhury (2014), Uppal and Mittal (2019) perceived dimensions of service quality have a strong impact on customers' complaining behaviour that can further be influenced by employees' attitudes. The study by Cruz and Mendes (2019) also concluded that users' satisfaction is the major determinant for their behavioural intentions. So, the present study also examines the relationship between customer behaviour intentions and the overall perceived service quality in the context of the Indian telecommunication industry.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 92%
See 2 more Smart Citations
“…According to Choudhury (2014), Uppal and Mittal (2019) perceived dimensions of service quality have a strong impact on customers' complaining behaviour that can further be influenced by employees' attitudes. The study by Cruz and Mendes (2019) also concluded that users' satisfaction is the major determinant for their behavioural intentions. So, the present study also examines the relationship between customer behaviour intentions and the overall perceived service quality in the context of the Indian telecommunication industry.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 92%
“…A positive score indicates that the service exceeds the customer's expectation, while a negative gap indicates that the actual service is of a lower level than expected. Negative gaps are the areas for improvement (Qadri, 2015;Lee et al, 2016;Cruz & Mendes, 2019). This concept forms the base for this theoretical framework.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction with BPJS patients must be maintained even though a standard inpatient class will be determined. Service quality influences customers' perceived value and satisfaction, resulting in greater loyalty, customer retention and attraction thereby increasing profitability (9). Service quality has been identified as a key service differentiator and a source of fundamental competitive advantage because companies always compete to a certain level of quality.…”
Section: Introductionmentioning
confidence: 99%